Jurnalisme Clickbait Di Era Digital: Mengungkap Strategi Pemilihan Diksi Judul Berita Oleh Detik.Com - Yasundari Yasundari; Fajarina Fajarina; Ballian Siregar; Olih Solihin; Safutra Rantona (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The rapid development of online media in Indonesia's digital era has introduced innovative ways of delivering information to readers. However, amidst this dynamism, the increasingly dominant phenomenon of clickbait has captured public attention. Clickbait, characterized by attention-grabbing and often enticing headlines, has become a common strategy employed by online media to attract visitors. This study delves into the impact of this phenomenon on information quality, journalistic ethics, and public trust in online media, with a specific focus on the strategies employed by Detik.com in selecting clickbait headline diction in January 2024. Through literature review analysis, the study aims to provide insights into the development of clickbait journalism, identify its impacts, and analyze the ethical aspects involved, contributing to a deeper understanding of the clickbait phenomenon in Indonesian online media.